Counseling on Wise Behavior in Choosing Safe and Halal Cosmetics for Supporting Healthy Facial Skin - Nurhabibah, Nurhabibah; Lubis, Novriyanti; Zafirah, Nadia Dewi; Agistin, Nayla Siti; Rachmat, Nazifa Meyla; Azarahra, Zulfa Ziana; Apriani, Shera Putri; Pramunawati, Widya (Fakultas Kewirausahaan Universitas Garut, 2025)
This counseling aimed to increase public knowledge and awareness about wise behavior in choosing safe and halal cosmetics to support skin health. Activities were conducted in two locations involving respondents through questionnaires. The data collected included knowledge of halal cosmetics, usage behavior, and awareness of product safety and halal labels. The results showed that most respondents had a good understanding of the definition, obligations, and characteristics of halal and safe cosmetics, with percentages above 75% in both locations. However, knowledge of the halal logo on packaging was relatively lower than other indicators. Most respondents already used halal cosmetics with 97.4% in Site 1 and 92.9% in Site 2, and tended to choose affordable products. This counseling highlight the importance of continuous education to strengthen public awareness in selecting halal and safe cosmetics to support skin health and comply with Islamic values.